McDaniels, John (audio interview #1 of 1) - McDaniels, John (5/9/1918 - 10/19/1998); Briegel, Kaye, interviewer
INTERVIEW DESCRIPTION - John McDaniels was interviewed in his home in Signal Hill. TOPICS - family background; childhood; oil industry; Depression; military; sports; the Pike; 1933 Long Beach earthquake; Richfield compressor plant explosion; WPA; and CCC;military; Kid Mexico; boxing; sports; US Army; petroleum refineries; and the Pike; 6/25/1991